Trends in caries experience and background factors in 3-year-old children in Poland: evidence from epidemiological surveys during 2002-2017 - Turska-Szybka Anna; Kaczmarek Urszula; Gozdowski Dariusz; Tomczyk Jacek; Olczak-Kowalczyk Dorota (Anthropological Review, 2019)
The prevalence of early childhood caries and its level varies. The present study was to establish the trends in dental caries and the impact of behavioural changes on the prevalence of caries in three-yearolds in Poland within a fifteen-year period. The results of a cross sectional survey carried out on 3439 three-year-olds in 2002, 2009, and 2017 using WHO criteria for dental caries (dmft, dmft=0, dmft≥4) and the results of a questionnaire filled by their parents with data on sociodemographics, oral hygiene and dietary habits, especially their sugar intake, were assessed. The dmft/dmfs index is applied to the primary dentition and is expressed as the total number of teeth/surfaces that are decayed, missing, or filled. The Cochran-Armitage test for trend was used to assess the fraction changes in time. The Pearson correlation coefficient was used to assess the changes in dmft trends and the correlations between behavioural changes, awareness levels, and the prevalence of caries. Within the fifteen-year period minimal changes in the prevalence of early childhood caries (15% down), dmft≥4 (11.4% down) and a lower dmft (36% down) were accompanied by a better parent awareness about the causes of caries and better oral hygiene routines. Sugary beverages were no longer drank at least once a day, however sweetened milk, cake, doughnuts, and sweet rolls were consumed more often. Being female, living in an urban area, having parents more aware about caries, consuming sugary beverages less frequently, brushing teeth twice a day, and using a fluoride toothpaste promoted lower early childhood caries. Gradually healthier teeth are linked to an increased awareness of the parents and healthier routines. A too frequent exposure to sugar promotes early childhood caries. Should the changes of dietary habits be insufficient, brushing teeth with fluoride toothpaste becomes crucial.